The Impact of Work Process Digitalization and Green HRM on Resource Efficiency at the South Labuhanbatu Bawaslu Secretariat - Ependi Pasaribu; Raden Lestari Ganarsih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the impact of work process digitalization and the implementation of Green Human Resource Management (HRM) on resource efficiency at the Bawaslu Secretariat in South Labuhanbatu Regency. As an election supervisory agency, Bawaslu faces challenges in efficiency, accountability, and speed of service, previously dominated by a paper-based administration system. This manual practice causes significant resource waste, both financially and environmentally. To address this, a digital transformation was carried out by developing an integrated administration management application that replaces physical documents with digital ones. This digitalization aims to cut lengthy bureaucracy and improve operational efficiency. The implementation of Green HRM at Bawaslu in South Labuhanbatu Regency is expected to reduce resource waste through the use of environmentally friendly and efficient technology. This study uses a literature review approach to identify and synthesize relevant previous research findings. The results show that the implementation of work process digitalization and Green HRM at Bawaslu in South Labuhanbatu Regency has had a positive impact on resource efficiency, by reducing paper, ink, and energy consumption, as well as increasing the accuracy and speed of administrative processes. In addition, the developed application also supports real-time data-based decision-making and increases transparency in election supervision